Eulogy in the Structure of Hieromonk Domentijan’s Hagiographies - Kostić Tmušić, Aleksandra S. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In Old Serbian Literature three types of genres can be distinguished: prose, poetry and transitional genres. Eulogy belongs to the transitional genres; in its structure both prose and poetic elements are contained. As a literary genre, eulogy is well developed in literary creations of almost all medieval writers. In this study, eulogies in hagiographies written by Hieromonk Domentijan are presented. In both of his works, Hagiography of Saint Sava and Hagiography of Saint Simeon, Domentijan brought eulogy in and developed it very well. The main goal of this paper is to present how and in which way, to what extent, eulogy, as a subgenre, is woven in the structure of a greater literary prose text. In the addition of the primary objective, the task is to analyze and interpret identified eulogies, in order to present its function in work of Hieromonk Domentijan in best manner.